STRATEGI PENGEMBANGAN KAWASAN PARIWISATA NASIONAL BOROBUDUR - Arif Sofianto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2018)
Borobudur area and its surroundings are one of the National Tourism Strategic Areas (KSPN). The government targets tourist arrivals to the Borobudur area to reach 2 million foreign tourists, and 11 million domestic tourists by 2019. On the other hand, the Borobudur Conservation Center (BKB) which is responsible for maintaining Borobudur Temple has made study that Borobudur's capacity is only 123 people rose above the temple in one time, and 528 people in the temple yard. This time, the number of tourists rose 10-fold, and there were indications of damage. In this regard, the purpose of this study is; 1) How is the solution to the management of Borobudur KSPN so that there is a sustainability side as well as the target of visits, 2) What role can the local government around the Borobudur area take to determine the status of the area and the strategic project to be implemented. This research was conducted using qualitative. Data is collected through interviews and direct observation, as well as tracking secondary data through various documents. Data analysis was performed using interactive analysis made by Miles & Huberman. The study was conducted around the Borobudur area, namely the Magelang Regency, Purworejo Regency, and Magelang City,. The conclusions of this study are: 1) the solution for managing the Borobudur tourist area is to change the mindset of tourism no longer centered on Borobudur Temple alone, the cultural and community landscape, and Borobudur making one of its parts. The tourism paradigm shifts from the monument-centric to the wider area and is no longer centralized, but the active involvement of the community. 2) Local governments (Magelang Regency, Purworejo Regency, and Magelang City) should improve with various supporting development programs in order to increase the acceleration of regional competitiveness and increase economic development opportunities to increase regional development and community welfare.